Strategi Guru Dalam Mengelola Manajemen Pendidikan Berbasis Seni - I Made Ardika Yasa; I Made Yudana (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2023)
Arts-based education has been recognized as a valuable approach in enriching students' learning experiences and developing their creativity. Teachers have a key role in managing effective arts-based education management. However, there is still limited research that specifically focuses on the strategies used by teachers in this context. Therefore, this study aims to identify and analyze the strategies used by teachers in managing arts-based education management. This study uses a qualitative method with a case study approach. Data was collected through classroom observations and interviews with art teachers who have experience in managing arts-based education management. Data analysis was carried out through coding and thematic processes. The results of the study show that there are several strategies used by teachers in managing art-based education management. First, the teacher uses a collaborative approach by actively involving students in the art learning process. Second, the teacher applies a differentiation approach to meet the different learning needs of each student. Third, teachers integrate the arts with the core curriculum to increase the relevance of learning. Fourth, teachers utilize technology in art learning to expand access and increase interaction between teachers and students. In conclusion, teachers have an important role in managing arts-based education management.